Inflation and economic growth: A review of the international literature - Foluso A. Akinsola; Nicholas M. Odhiambo (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper surveys the existing literature on the relationship between inflation and economic growth in developed and developing countries, highlighting the theoretical and empirical indications. The study finds that the impact of inflation on economic growth varies from country to country and over time. The study also finds that the results from these studies depend on country-specific characteristics, the data set used, and the methodology employed. On balance, the study finds overwhelming support in favour of a negative relationship between inflation and growth, especially in developed economies. However, there is still much controversy about the specific threshold level of inflation that is appropriate for growth. Most previous studies on this subject just assume a unidirectional causal relationship between inflation and economic growth. To our knowledge, this may be the first review of its kind to survey, in detail, the existing research on the relationship between inflation and economic growth in developed and developing countries.
Keywords: E31; O42; O47; 330; inflation; economic growth; developed countries; developingcountries